Microalgae as feed ingredients for livestock production and meat quality: A review - Madeira, Marta S.; Cardoso, Carlos; Lopes, Paula A.; Coelho, Diogo; Afonso, Cláudia; Bandarra, Narcisa M.; Prates, José A.M. (Livestock science, 2017)
Microalgae, small-sized algae, have been studied as a natural marine resource for a number of economically relevant applications, including animal feed. In this review, we unveil the dietary microalgae effects currently known on production and meat quality of livestock species (ruminants, pigs, poultry and rabbits). Microalgae are classified into diatoms (Bacillariophyceae), green algae (Chlorophyceae), golden algae (Chrysophyceae) and blue-green algae cyanobacteria (Cyanophyceae). The most important phototrophic species belong to Arthrospira, Chlorella, Dunaliella and Haematocussus genus. In addition, heterotrophic marine organisms, such as Crypthecodinium, Schizochytrium and Ulkenia, have been successfully cultivated for n-3 long-chain polyunsaturated fatty acids (n-3 LCPUFA) production. Microalgae are mainly composed by proteins, carbohydrates, lipids, vitamins, minerals and bioactive compounds, such as carotenoids. This variable nutrient composition depends on species, strain and algae growing conditions. Research evidence so far has shown that the inclusion of microalgae in animal diets could improve growth and meat quality in ruminants, pigs, poultry and rabbits. These findings are highly dependent on microalgae own composition and their amount in the diet. In a general overview, the inclusion of Arthrospira platensis in pig and poultry diets increases average daily gain but negatively affects feed conversion ratio. Regarding Schizochytrium sp., this microalga improves fatty acid composition in pork and poultry meat, essentially due to its high content in docosahexaenoic acid (DHA). Chlorella, at very low percentages in feed, benefits growth performance parameters of poultry. The use of microalgae as feed ingredients is very promising as an alternative to corn and soybean, thus mitigating the current competition among food-feed-biofuel industries. In addition, microalgae contribute for the protection of environment and natural resources, namely land degradation and water deprivation. Microalgae also provide a sustainable alternative for n-3 LCPUFA availability, thus protecting worldwide fatty fish stocks. However, the cost-effective production and use of microalgae is a major challenge in the near future. In fact, the current microalgae cultivation technology should be improved to reduce their production costs. In addition, we foresee that the efficiency of microalgae incorporation in monogastric diets could be largely improved by the use of Carbohydrate-Active enZymes (CAZymes). CAZymes will allow the increase of nutrients bioavailability, as a consequence of recalcitrant microalgae cell walls degradation. Overall, the inclusion of microalgae in feed represents a very promising strategy for the maintenance and development of livestock sector, as an environmental friendly alternative to balance food-feed-biofuel industries. •The use, potential and constraints of microalgae in livestock diets is reviewed.•Inclusion of microalgae in feed could improve animal growth and meat quality.•Microalgae are very promising alternatives to staple food crops in feeds.•Microalgae could help the sustainability of livestock production systems.•The cost-effective use of microalgae is a major challenge for animal feeding.